Ricomporre i frammenti.: Montaggio e memoria in Aftersun di Charlotte Wells (PHILM. Rivista di filosofia e cinema, 2024)
This article seeks to examine the role of montage in Charlotte Wells’ Aftersun (2022) in relation to the film’s need to reconstruct a visual recollection of memory. A comparison with Proust’s mémoire involontaire and its benjaminian reinterpretation will demonstrate the capacity of montage to transcend its conventional narrative function (to link the constituent elements of a narrative together as to restore its continuity) and to fully harness the potential for establishing temporal connections between images.